Tribological characteristics and performances of modified palm kernel and palm stearin as alternative lubricant - Nurul Farhanah Azman, 1991-, author 606612; Syahrullail Samion, supervisor 495611; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Kejuruteraan (Mekanikal))